STRATEGI PENGAWASAN DINAS PENDAPATAN DAERAH TERHADAP PEMASANGAN REKLAME KOMERSIAL DI KOTA PONTIANAK - Akhmad Syafrandana E.21108006 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
Issues regarding the number of billboards that have sprung up in various forms, it is very possible breaches of the installation of billboards. Methods This study is a descriptive research research that can be interpreted as a problem-solving procedure is investigated by describing or depicting the state of the subject and object of research at the present time based on the facts that appear or as they are. The purpose of this study to describe the strengths, weaknesses, opportunities and challenges of Pontianak revenue to the commercial installation of billboards in the city of Pontianak and to describe the strategies and the efforts undertaken by the Regional Revenue Office of Pontianak in supervising and regulating the installation of billboards. This could be a lesson that there is less power is maximized to minimize weaknesses. It is expected that this analysis will continue to try and increase the strength of revenue by optimally so that weaknesses can be overcome. Strategy and the efforts undertaken by the Regional Revenue Office of Pontianak in supervising and regulating the installation of billboards already well underway. But there are still obstacles, including lack of equipment and lack Officer. Ability or competence of staff support for the officers felt not maximized. This can be seen from the Section II Field and floating. Keywords: Control, Strategy, Advertising, Commercial.